Dilemma of Facedness and Facelessness in the Social-Cultural Context of Mass Society - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
The article considers the problem of transformation of individuality in the social-cultural context of contemporary mass society. One of the peculiar social-cultural characteristics of contemporary word is that the individual is viewed as a social creature that has individuality. However the contemporary man who has the right of being individuality runs into defacing, one-dimensionalising elements of mass culture which has emerged as a result of some civilizational, political and cultural transformations. Regularities peculiar to the crowd function within mass culture and as a result being subjected to dissolving, defacing influence of mass crowd one encounters the risk of losing the uniqueness of one’s own face.